Enhancing students critical thinking skills and confidence in learning biology through dialogic teaching - Reyes, Odessa Valeza (College of Education, University of the Philippines Diliman, 2020)
This study investigated the effects of Dialogic Teaching on the students critical thinking skills and confidence in learning biology, as well as, the relationship between confidence in learning biology and critical thinking skills. A quasi-experimental inquiry with pretest-posttest two-group design was implemented randomly assigning one group to the Non-Dialogic Teaching Approach group and the other to the Dialogic Teaching Approach group. The study was conducted during the 3rd quarter of Academic Year 2018-2019 with a focus on topics set by the K to 12 curriculum. The sample included fifty (50) Grade 10 students from a public general high school in Quezon City. It adapted two instruments: Biology-Based Critical Thinking Appraisal and Student Confidence Scale. Both instruments were validated by experts and pilot tested among thirty-one (31) students in Grade 11. The comparison data between the pretest and posttest scores of both groups were analyzed using independent samples t-test. A linear regression analysis was also conducted to determine the relationship between confidence in learning Biology and critical thinking skills. The findings of the study revealed that the Dialogic Teaching Approach group is better in terms of critical thinking skills and confidence in learning biology than the Non-dialogic Teaching Approach group. Furthermore, critical thinking skills are found to be a positive predictor of confidence in learning biology and vice versa. Based on the results, the researcher concludes that Dialogic Teaching has a positive impact on students critical thinking skills and confidence in learning biology. It is, therefore, recommended that the approach be explored further by looking into its impact on other student skills and on teacher skills. It also supports the use of the Dialogic Teaching approach in schools to help develop the students critical thinking skills and confidence in learning biology.